Advances and challenges of mpox detection technology - Wenjing Liu; Erxin Zhang; Wei Li; Ruichen Lv; Yanfeng Lin; Yingjia Xu; Jiameng Li; Yuzhen Lai; Yuxin Jiang; Sijia Lin; Xueqin Wang; Peize Zhou; et al. (Elsevier, 2024)
Mpox is a zoonotic disease caused by the monkeypox virus (MPXV). Diagnosing and treating the disease has become a global health concern requiring close attention to its spread to non-endemic regions. Clinical diagnosis is based on laboratory test results. Conventional detection techniques include real-time quantitative polymerase chain reaction (qPCR), genome sequencing, antigen and antibody identification, and virus isolation. Nevertheless, these methods fall short of rapidly and efficiently identifying MPXV, as they require specialized training, specific laboratory environments, and professional-grade equipment. Emerging technologies offer complementary advantages to meet diverse diagnostic needs, including various point-of-care testing (POCT) approaches and integrating biosensors with rapid detection techniques. This review discusses prospective future research avenues for MPXV detection, examining the advances and challenges of various detection techniques which may contribute to the ongoing elimination of mpox human-to-human transmission and serves as a reference for developing effective prevention and control strategies.